A rapid, accurate, and low-cost method for detecting Mycobacterium tuberculosis and its drug-resistant genes in pulmonary tuberculosis: Applications of MassARRAY DNA mass spectrometry - Yang, Han; Li, Aifang; Dang, Liyun; Kang, Tao; Ren, Fei; Ma, Jinbao; Zhou, Yong; Yang, Yuanli; Lei, Jing; Zhang, Tao (Frontiers in Microbiology, 2023)
Mycobacterium tuberculosis (MTB) identification and drug resistance diagnosis are very important for treatment of drug-resistant tuberculosis (DR-TB). Therefore, high throughput, accurate and low-cost molecular detection techniques are urgently needed. This study aimed to evaluate the clinical application value of MassARRAY in tuberculosis diagnosis and drug resistance screening. The limit of detection (LOD) and clinical application value of MassARRAY were evaluated using reference strains and clinical isolates. In MassARRAY, 20 related gene mutations could be detected by two polymerase chain reaction (PCR) systems. All genes could be accurately detected when the bacterial load was 104 CFU/mL. When the load of wild-type and drug-resistant MTB mixture was 105 CFU/mL (respectively reached 104 CFU/mL), variants and wild-type genes could be detected simultaneously. The sensitivity of MassARRAY (96.9%) for identification was higher than that of real-time PCR (87.5%) (P < 0.001). The sensitivity and specificity of MassARRAY for all drug resistance gene mutations were 100.0%, with higher accuracy and consistency than the high-resolution melting curve method (sensitivity = 89.3% and specificity = 96.9%, P = 0.001). Analyzing the relationship between MassARRAY genotype and drug susceptibility testing (DST) phenotype, the accuracy of katG_315, rpoB_531, rpsL_43, rpsL_88 and rrs_513 sites was 100.0%, and embB_306 and rpoB_526 were inconsistent with the DST results when the base changes were different. MassARRAY can obtain base mutation information and identify heteroresistance infections simultaneously when the mutant proportion was at least 5%–25%. It has good application prospects in the diagnosis of DR-TB with high throughput, accurate and low-cost.